Histological Correlates of Neuroanatomical Changes in a Rat Model of Levodopa-Induced Dyskinesia Based on Voxel-Based Morphometry - Zhang, Xiaoqian; Chen, Wei; Wu, Yi; Zeng, Weiqi; Yuan, Yuhao; Cheng, Chi; Yang, Xiaoman; Wang, Jialing; Yang, Xiaomei; Xu, Yu; Lei, Hao; Cao, Xuebing; et al. (Frontiers in Aging Neuroscience, 2021)
Long-term therapy with levodopa (L-DOPA) in patients with Parkinson’s disease (PD) often triggers motor complications termed as L-DOPA-induced dyskinesia (LID). However, few studies have explored the pathogenesis of LID from the perspective of neuroanatomy. This study aimed to investigate macroscopic structural changes in a rat model of LID and the underlying histological mechanisms. First, we established the hemiparkinsonism rat model through stereotaxic injection of 6-hydroxydopamine (6-OHDA) into the right medial forebrain bundle, followed by administration of saline (PD) or L-DOPA to induce LID. Magnetic resonance imaging (MRI) and behavioral evaluations were performed at different time points. Histological analysis was conducted to assess the correlations between MRI signal changes and cellular contributors. Voxel-based morphometry (VBM) analysis revealed progressive bilateral volume reduction in the cortical and subcortical areas in PD rats compared with the sham rats. These changes were partially reversed by chronic L-DOPA administration; moreover, there was a significant volume increase mainly in the dorsolateral striatum, substantia nigra, and piriform cortex of the lesioned side compared with that of PD rats. At the striatal cellular level, glial fibrillary acidic protein-positive (GFAP+) astrocytes were significantly increased in the lesioned dorsolateral striatum of PD rats compared with the intact side and the sham group. Prolonged L-DOPA treatment further increased GFAP levels. Neither 6-OHDA damage nor L-DOPA treatment influenced the striatal expression of vascular endothelial growth factor (VEGF). Additionally, there was a considerable increase in synapse-associated proteins (SYP, PSD95, SAP97) in the lesioned striatum of LID rats relative to the PD rats. Golgi-Cox staining analysis of the dendritic spine morphology revealed an increased density of dendritic spines after chronic L-DOPA treatment. Taken together, our findings suggest that striatal volume changes in LID rats involve astrocyte activation, enrichment of synaptic ultrastructure and signaling proteins in the ipsilateral striatum. Meanwhile, the data highlight the enormous potential of structural MRI, especially VBM analysis, in determining the morphological phenotype of rodent models of LID.